2014
DOI: 10.1038/ncomms6426
|View full text |Cite
|
Sign up to set email alerts
|

Rad54B serves as a scaffold in the DNA damage response that limits checkpoint strength

Abstract: The strength of the DNA damage checkpoint critically influences cell fate, yet the mechanisms behind the fine tuning of checkpoint strength during the DNA damage response (DDR) are poorly understood. Here we show that Rad54B-a SNF2 helicase-like DNA-repair protein-limits the strength of both the G1/S and G2/M checkpoints. We find that Rad54B functions as a scaffold for p53 degradation via its direct interaction with the MDM2-MDMX ubiquitin-ligase complex. During the early phases of the DDR, Rad54B is upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Clearly, further work is required to clarify the mechanism of Rad54/Rad54B‐independent gene targeting in human cells, the occurrence of which is demonstrated in our present study. It will also be important to elucidate the exact roles of Rad54B in preserving genome integrity, as this protein has recently been reported to promote genomic instability via the degradation of p53 protein . Interestingly, the combined absence of Rad54B and DNA ligase IV in HCT116 cells is synthetically lethal .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, further work is required to clarify the mechanism of Rad54/Rad54B‐independent gene targeting in human cells, the occurrence of which is demonstrated in our present study. It will also be important to elucidate the exact roles of Rad54B in preserving genome integrity, as this protein has recently been reported to promote genomic instability via the degradation of p53 protein . Interestingly, the combined absence of Rad54B and DNA ligase IV in HCT116 cells is synthetically lethal .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yasuhara et al identified a novel role for RAD54B in cell cycle checkpoint regulation. More specifically, they showed that following DNA damage induced by Oxaliplatin, RAD54B expression levels increased and were inversely correlated with p53 levels, suggesting RAD54B regulates p53 levels . They further showed that RAD54B acts as a scaffolding protein and physically interacts with the MDM2/MDMX ubiquitin ligase complex.…”
Section: Rad54b Is a Scaffold Protein Involved In Cell Cycle Checkpoimentioning
confidence: 99%
“…Based on the inverse relationship observed between RAD54B and p53, it's not difficult to envision how RAD54B overexpression could lead to abnormal scaffolding of the MDMX/MDM2 ubiquitin ligase complex to induce premature p53 degradation that would adversely impact normal cell cycle regulation and progression. Indeed, RAD54B overexpression effectively suppresses the G1/S checkpoint and promotes checkpoint override (Figure B) to drive oncogenesis . Moreover, high RAD54B expression levels during G2 can result in the bypass of the G2 checkpoint in a process referred to as checkpoint adaptation.…”
Section: Rad54b Is a Scaffold Protein Involved In Cell Cycle Checkpoimentioning
confidence: 99%
See 2 more Smart Citations